Case Report: Rotavirus Vaccination and Severe Combined Immunodeficiency in Japan - Tanita, Kay; Kawamura, Yoshiki; Miura, Hiroki; Mitsuiki, Noriko; Tomoda, Takahiro; Inoue, Kento; Iguchi, Akihiro; Yamada, Masafumi; Yoshida, Taro; Muramatsu, Hideki; Tada, Norimasa; Matsui, Toshihiro; et al. (Frontiers in Immunology, 2022)
Severe combined immunodeficiency (SCID) is an inborn error of immunity that occurs in approximately 1 in 50,000 births, mainly due to impaired lymphocyte differentiation. Without curative treatment, such as hematopoietic cell transplantation (HCT) or gene therapy, severe infection in the first year of life could make this condition fatal. The results of HCT are poor when patients have active infections; thus, requiring early diagnosis before onset of infection. In five cases of SCID diagnosed in Japan, the oral rotavirus vaccine had been administered before diagnosis. In this study, we demonstrated that the rotavirus from their stools was a vaccine-derived strain. In some cases, severe gastroenteritis triggered the diagnosis of SCID. However, newborn screening for SCID is available before the first rotavirus vaccination using assays for the detection of T-cell receptor excision circles (TRECs). Therefore, to improve the prognosis of patients with SCID in Japan, we should establish a screening system of TRECs for newborns throughout Japan.